Orientation Independent Chipless RFID Tag Using Novel Trefoil Resonators - Tariq N; Riaz MA; Shahid H; Khan MJ; Khan MS; Amin Y; Loo J; Tenhunen H (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
In this paper, a compact and fully passive bit encoding circuit, capable of operating as a chipless radio frequency identification (RFID) tag is presented. The structure consists of novel concentric trefoil-shaped slot resonators realized using Rogers RT/duroid (R) 5880 laminate, occupying a physical footprint of 13.55 x 13.55 mm(2). Each resonating element is associated with a particular data bit, having a 1:1 resonator-to-bit correspondence. Bit sequences are configured through introducing modifications in the geometric structure either by addition or exclusion of each nested slot resonator. Such changes manifest directly in the electromagnetic signature of the tag as presence or absence of corresponding resonant peaks. The proposed 10-bit tag offers minimized inter-resonator mutual coupling and insensitivity to changes in polarization and incident angles thereby demonstrating orientation independent functionality. Moreover, error-free encoding is achieved through stabilizing the shift in resonant frequencies for a variety of different geometric configurations and orientation of the structure. The tag operates within the license-free ultrawideband ranging from 5.4 to 10.4 GHz, providing spectral bit capacity and bit density of 2 bits/GHz and 5.44 bits/cm(2) respectively.